2021
DOI: 10.1093/isr/viaa092
|View full text |Cite
|
Sign up to set email alerts
|

The Return of National Self-Sufficiency? Excavating Autarkic Thought in a De-Globalizing Era

Abstract: As the global crisis triggered by the COVID-19 virus unfolded, The Economist magazine published a cover in May 2020 titled “Goodbye globalization: the dangerous lure of self-sufficiency.” The title summed up well the new political interest in the ideology of national economic self-sufficiency in the pandemic context. Unfortunately, contemporary textbooks in the field of international political economy (IPE) say little about this kind of “autarkic” thought. No survey of the history of autarkic thought exists ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
0
10
0
3
Order By: Relevance
“…Foreign influence, particularly if feared to be troublesome, was to be kept at the shore of the Japanese territory – be it on a cruise ship. The same strategy was applied during the actual sakoku (“closed country”) period, when a small number of foreigners were allowed to reside for trading and educational purposes on Dejima Island, an artificially constructed island in Nagasaki Bay, and therefore not on Japanese soil ( Helleiner, 2021 ; Palmer, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Foreign influence, particularly if feared to be troublesome, was to be kept at the shore of the Japanese territory – be it on a cruise ship. The same strategy was applied during the actual sakoku (“closed country”) period, when a small number of foreigners were allowed to reside for trading and educational purposes on Dejima Island, an artificially constructed island in Nagasaki Bay, and therefore not on Japanese soil ( Helleiner, 2021 ; Palmer, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…«This reversal of fortunes constitutes perhaps the most momentous global economic change in the last 100 years» (Baldwin, 2012, p. 13). Yet, events such as the pandemic and the Russian-Ukrainian war have now put the self-reliance of nations on the agenda, raising the question of a return to autarchy, understood as an extreme form of inward-centered economic nationalism, which results in minimizing international economic linkages (Helleiner, 2021) and, therefore, the above-mentioned benefits. And sadly, when economic nationalism meets ascendant populism, any rational utilitarian cost-benefit weighting that also incorporates externalities vanishes.…”
Section: In Search Of Effective Economic and Industrial Policiesmentioning
confidence: 99%
“…Along this continuum, various approaches have emerged in the history of economic thought. Helleiner (2021) pointed out how the nineteenth-century German thinker Friedrich List (1841) put forward a neo-mercantilist version of economic nationalism as an alternative to autarky, which seeked to promote domestic industries capable of competing successfully in an open world economy. This activist outwardlooking policy was re-proposed by Chang (2002) and Reich (1991), who argued that national interests can be better served by state investments in education, infrastructure and other public goods that are able to enhance the competitiveness of domestic firms.…”
Section: In Search Of Effective Economic and Industrial Policiesmentioning
confidence: 99%
“…Third, foreign protectionism may increase the perceived economic and political costs that accompany a strategy of open trade. The adoption of protectionism by a foreign state is likely to cause “citizens to recognize in a much more serious way how economic interdependence left them vulnerable to international markets and the actions of foreign governments” (Helleiner, 2021 , 19). For these reasons, protectionism in foreign countries is likely to increase support for trade barriers on both a bilateral and a global basis.…”
Section: The Impact Of Foreign Protectionism On Public Support For Op...mentioning
confidence: 99%
“…Much like China, part of India’s official response involved retaliatory tariffs on US goods (BBC, 2019 ). Indian Prime Minister Narendra Modi also concluded that US protectionism necessitated a broader reorientation of trade policy, asserting in a speech in May 2019 that the “state of the world today teaches us that ‘Self-reliant India’ is the only path” (quoted in Helleiner, 2021 , 19). We anticipate that ordinary citizens will respond to foreign protectionism in a similar manner as policymaking elites, favoring higher trade barriers on both a bilateral and systemic basis.…”
Section: The Impact Of Foreign Protectionism On Public Support For Op...mentioning
confidence: 99%